Was macht die Digitalisierung mit den Hochschulen? Einwürfe und Provokationen - Demantowsky, Marko (De Gruyter, 2020)
What will become of successful universities once everything is digitalized? Experts from schools and universities, policymakers, journalists, and computer scientists present their responses, expectations, and trepidations, under the overarching premise of humanely shaping the digital revolution. The essays were developed from the course "Humans/Machines/The Future" presented in 2019 at the former Diessen cloister in Ammersee.